2014
DOI: 10.1242/jeb.091249
|View full text |Cite
|
Sign up to set email alerts
|

Transcellular chaperone signaling: an organismal strategy for integrated cell stress responses

Abstract: The ability of each cell within a metazoan to adapt to and survive environmental and physiological stress requires cellular stressresponse mechanisms, such as the heat shock response (HSR). Recent advances reveal that cellular proteostasis and stress responses in metazoans are regulated by multiple layers of intercellular communication. This ensures that an imbalance of proteostasis that occurs within any single tissue 'at risk' is protected by a compensatory activation of a stress response in adjacent tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 106 publications
(110 reference statements)
1
24
0
Order By: Relevance
“…The observation that the depletion of sip1 already leads to a stress response in the worm (as visible by the overexpression of the hsp16 genes), might explain why a further stress situation, like heat stress or aging, has severe effects on embryonic and adult worms. In the worm, it has been shown that there is a crosstalk between different tissues and organs concerning the stress status (van Oosten-Hawle and Morimoto, 2014). In agreement to the present study, this seems to apply for the reproductive tissue of the adult and the embryo.…”
Section: Discussionsupporting
confidence: 91%
“…The observation that the depletion of sip1 already leads to a stress response in the worm (as visible by the overexpression of the hsp16 genes), might explain why a further stress situation, like heat stress or aging, has severe effects on embryonic and adult worms. In the worm, it has been shown that there is a crosstalk between different tissues and organs concerning the stress status (van Oosten-Hawle and Morimoto, 2014). In agreement to the present study, this seems to apply for the reproductive tissue of the adult and the embryo.…”
Section: Discussionsupporting
confidence: 91%
“…The activation of HSF-1, the key transcription factor of Hsp72, is a multistep process involving multiple regulators that might be independently regulated by factors prevalent in PDF. 48,49 O-GlcNAc-mediated regulation of HSF-1 is also supported by the recent work by Kazemi et al, 23 which reported a link between Hsp72, HSF-1, glycogen synthase kinase 3b, and O-GlcNAcylation. Recently, we have shown that the addition of glutamine to PDF protects mesothelial cells in in vitro and in vivo models of PD by enhancing CSRs after PDF exposure.…”
Section: Discussionmentioning
confidence: 56%
“…C. elegans has no known dedicated, migratory immune cells like macrophages to aid in defense against infection of the intestine or epidermis, and does not appear to have canonical cytokine and chemokine signaling pathways used to recruit those cells. However, C. elegans does use system-wide signaling to respond to stress and infection by upregulating defense pathways in epithelial cells, which is a topic that has been covered in other reviews [9,12,18-21]. …”
Section: Background On C Elegans Infections and Host Defensementioning
confidence: 99%